The Role of DNA in the Extracellular Environment: A Focus on NETs, RETs and Biofilms - Monticolo, Francesco; Palomba, Emanuela; Termolino, Pasquale; Chiaiese, Pasquale; de Alteriis, Elisabetta; Mazzoleni, Stefano; Chiusano, Maria Luisa (Frontiers in Plant Science, 2020)
The capacity to actively release genetic material into the extracellular environment has been reported for bacteria, archaea, fungi, and in general, for microbial communities, but it is also described in the context of multicellular organisms, animals and plants. This material is often present in matrices that locate outside the cells. Extracellular matrices have important roles in defence response and disease in microbes, animal and plants cells, appearing as barrier against pathogen invasion or for their recognition. Specifically, neutrophils extracellular traps (NETs) in animals and root extracellular traps (RETs) in plants, are recognized to be important players in immunity. Recently, A growing amount of evidence revealed that the extracellular DNA, in these contexts, plays an active role in the defence action. Moreover, the protective role of extracellular DNA against antimicrobials and mechanical stress also appears to be confirmed in bacterial biofilms. In parallel, recent efforts highlighted different roles of self (homologous) and nonself (heterologous) extracellular DNA, paving the way to discussions on its role in ”Damage-associated molecular patterns” (DAMP). We here provide an evolutionary overview on extracellular DNA in extracellular matrices like RETs, NETs and microbial biofilms, discussing on its roles and inferring on possible novel functionalities.